Ectopic Thyroid Presenting as a Sublingual Mass in a Sudanese Girl - Osman, Wail N; Elmustafa, Osman M (Gezira Journal of Health Sciences, 2012)
Although extremely rare, the presence of ectopic thyroid tissue in the sublingual region should be considered in the differential diagnosis of masses in the cervical region. Diagnosis is confirmed by Fine-needle Aspiration\Biopsy Cytology and exclusion of malignancy by histopathologic analysis of the lesion. In general, surgery should not be attemptrd before radioisotope scan is obtained as this might be the only functioning thyroid tissue.  This is a rare case of ectopic thyroid in the sublingual region reported in a Sudanese girl; it was diagnosed after radioisotope thyroid scan and proved to be the only functioning thyroid tissue.